(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The sporting environment is a rich, unique, and salient context in which to study the basic and applied nature of a variety of social dynamics. Issues such as leadership, collective efficacy, team cohesion, and group goal setting undoubtedly have great theoretical and practical value within sport teams. Sport is completely permeated by the question of the diversity which it vividly enacts. The same way sports blends sporting spirit, competition drive and fair play it should also blend culturally different envisaged notions of non-uniformity, diversity, enrichment through other culture, other skin color, other language and other style of living. All disciplines are concerned to a more or less intense degree, depending on their popular support or lack of it and on the culture which they convey. Multiple origins and complex careers are now a hallmark: handball, rugby, basketball as well as individual sports like athletics, judo and tennis have their champions stemming from diversity, who form the tip of an equally variegated iceberg of school and amateur sport (Diamond P., Hausman J., 1994).